Assessing the credibility of how climate adaptation aid projects are categorised. Issue 4 (19th May 2017) - Weikmans, Romain; Timmons Roberts, J.; Baum, Jeffrey; Bustos, Maria Camila; Durand, Alexis
ABSTRACT: This article presents the findings of a re-evaluation of all 5, 200 aid projects that OECD donors reported for 2012 as "climate change adaptation"-related, based on the "Rio marker" classification system. The findings confirm those from the academic and grey literature that the absence of independent quality control makes the adaptation Rio marker data almost entirely unreliable. This lack of credibility impedes meaningful assessments of progress toward the mainstreaming of adaptation in development cooperation activities. It also erodes trust in international climate negotiations, given that these data are frequently used in the financial reporting of developed countries to the UNFCCC.